Groundwater Quality Assessment and Health Risks from Fluoride in Jamui, Bihar - Neeti, Krishna; Singh, Reena (Engineering, Technology & Applied Science Research, 2023)
This study aimed to determine the fluoride concentration in drinking water and assess its health risks by analyzing 12 physicochemical parameters, including fluoride, pH, EC, TDS, chloride, carbonate and bicarbonate (alkalinity), sulfate, nitrate, calcium, and magnesium hardness. Correlation analysis, WQI, and HRA were used to determine whether groundwater in the study area was suitable for drinking. Correlation analysis showed that fluoride was negatively correlated with EC (-0.649), CO32- (-0.855) and positively correlated with Mg2+ (+0.559). All water samples exceeded the permissible fluoride limits according to BIS (IS 10500:2012). The WQI for all water samples was more than 100, indicating that the water was not suitable for drinking. Health risk assessment was also performed to determine the risks of non-carcinogenic diseases. The Hazard Index (HI) was determined as greater than 1. The HI ranged from 1.275 to 3.346 for adult men, 1.431 to 3.954 for adult women, and 1.986 to 5.4864 for children. Fluoride concentrations in drinking water pose a greater health risk to children than to adults. The fluoride level in drinking water is an essential parameter that must be monitored as a preventive measure against dental and skeletal fluorosis.